Industrial training report: Medical Record Services, KPJ Bandar Maharani Specialist Hospital / Ummi Fatihah Mohd Yunus - Mohd Yunus, Ummi Fatihah (Bachelor of Information Science (Hons.) Records Management, 2015)
Appraisal process is the steps to identify records which should be retained long term or permanently for legal value. During my practical period, I am required to do the report about appraisal process and disposition process. In this report, I can highlight the challenges for encountered and the solution for the problem that are occurs during the time. In all the medical records process, there must have the appraisal and disposal records. So, this report contains the methods to implement the appraisal and disposition process that can be implement in this hospital. This report to be presented as a proposal for this hospital when they want to implemented in the future. This report also contain all the activities during the practical period.